Fkdiff: An Efficient Diffusion Model for Image Super-Resolution With Fourier Frequency Domain Transformation and Knowledge Distillation - Chen, Yu (International Journal of Computer Science and Information Technology, 2024)
Image super-resolution (SR) techniques play a crucial role in various applications such as image restoration, medical imaging, surveillance, and remote sensing. Traditional methods often employ interpolation algorithms to upscale images, resulting in artifacts and reduced perceptual quality. Recent advancements in diffusion models (DM) have shown promising results in image generation tasks but are hindered by computational complexity, particularly in resource-constrained environments. By leveraging low-resolution images as prior information and operating in the frequency domain, FKdiff achieves enhanced computational efficiency and preserves high-frequency details effectively. The proposed method integrates a progressive hexagonal knowledge distillation (PHexKD) approach, ensuring lightweight model deployment without compromising performance. Experimental results demonstrate that FKdiff outperforms existing methods in terms of efficiency and effectiveness while a small amount of image generation quality is lost.